P0286B CELL REPOPULATION AFTER REMISSION INDUCTION WITH RITUXIMAB IN NEWLY DIAGNOSED PATIENTS WITH ANCA-ASSOCIATED VASCULITIS: DOES ONE SIZE FIT ALL?. (6th June 2020) - Salviani, Chiara; Gregorini, Alessandra Gina; Jeannin, Guido; Alberici, Federico; Cancarini, Giovanni; Scolari, Francesco
Abstract: Background and Aims: Rituximab (RTX) is one of the mainstays of ANCA-associated vasculitis (AAV) treatment. Nevertheless, studies specifically addressing the B cell repopulation in AAV patients after remission induction with RTX are still scanty and with conflicting results. Moreover, the role of B cell monitoring in the management of RTX-based maintenance therapy still remains to be fully elucidated. In this study, we evaluated B cell repopulation after a single course of RTX in treatment-naïve patients with AAV. Method: We included all consecutive patients with new diagnosis of AAV from December 2009 to December 2017, treated with a single course of RTX for remission induction, with a follow-up ≥12 months. B cell recovery, re-treatment for relapse or rise in ANCA titer and scheduled re-treatment were considered as the termination of observation period. B cell count was performed by flow cytometry (Beckman Coulter Navios©) every 2 weeks during the 1 st month, every 4 weeks until the 6 th month, then every 12 weeks. B cell recovery was defined as CD19 count ≥10 cells/μl. Results: Seventy-four patients (38% M, 62% F) met the inclusion criteria. Mean age was 63±21 years. MPA, GPA and EGPA were diagnosed in 49 (66%), 24 (33%) and 1 (1%) patients, respectively. ANCA were positive in 65 (88%) patients, with 50 (68%) anti-MPO and 15 (20%) anti-PR3. Overall median follow-up was 40 months (IQR 25-60). All patients achieved remission and complete B cell depletion after RTX. Twenty-two (31%) patients received plasma-exchange and 20 (29%) steroid pulses. Maintenance therapy with azathioprine or methotrexate was started in 10 (14%) patients. Seventeen (23%) patients received re-treatment with RTX (10 patients for relapses, the remaining cases for B cell recovery and/or a rise in ANCA titre or scheduled re-treatment). B cell recovery was observed in 39 (53%) patients, after a median time of 27 months (IQR 20-38). Particularly, only 7% of patients recovered B cells at 12 months (Figure 1). Univariate analysis showed significant correlation of persistent B-cell depletion with diagnosis of MPA vs GPA (p<0.001), ANCA anti-MPO vs anti-PR3 (p=0.009), higher serum creatinine (p<0.0001) and older age (p=0.004) (Figure 2). Sex, plasma-exchange at induction, steroid pulses, cumulative dose of RTX and maintenance therapy did not affect B cell recovery. Multivariate analysis confirmed significant association between B cell recovery and better renal function (RR 2.655, IC 1.254-5.615, p= 0.011) and clinical diagnosis of GPA (RR 2.466, IC 1.211-5.021, p=0.013). Conclusion: After a single course of RTX for remission induction, we observed a very long-lasting B cell depletion in the large majority of our patients. Clinical diagnosis of MPA and a worse renal function were significantly correlated to persistent B cell depletion. These data question the need for scheduled RTX re-treatments in all AAV patients regardless of clinical diagnosis and features.